Kinetics of Oxidation of 3-Benzoylpropionic Acid by N-Bromoacetamide in Aqueous Acetic Acid Medium - N. A. Mohamed Farook; G. A. Seyed Dameem (E-Journal of Chemistry)
The kinetics of oxidation of 3-benzoylpropionic acid (KA) with N-bromoacetamide (NBA) have been studied potentiometrically in 50:50 (v/v) aqueous acetic acid medium at 298 K The reaction was first order each with respect to [KA], [NBA] and [H+]. The main product of the oxidation is the corresponding carboxylic acid. The rate decreases with the addition of acetamide, one of the products of the reaction. Variation in ionic strength of the reaction medium has no significant effect on the rate of oxidation. But the rate of the reaction is enhanced by lowering the dielectric constant of the reaction medium. A mechanism consistent with observed results have been proposed and the related rate law was deduced.